ความเชื่อมโยงระหว่างชนบทและเมืองในพื้นที่ขยายตัวของอภิมหานครกรุงเทพ ของอุตสาหกรรมขนาดเล็กในชนบท : กรณีศึกษาจังหวัดปทุมธานี - เปี่ยมสุข สนิท (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Pathum Thani, located directly north of Bangkok along the Highway no.1 (Phaholyothin Road), is a part of the extended metropolitan region along main roads. According to McGee, this area is called Desakota zone . One of the characteristics of the Desakota zone is that there are intensely mixed land uses between agricultural and non-agricultural activities. The objective of the research is to study on the linkages between rural and urban areas which are effects of the production of small-scale manufacturing in rural Pathum Thani, based on the Forward and Backward Production Linkages concept. A survey is conducted using questionnaire and interview methods to gather data from entrepreneurs in the study area. The research finds that the rural small-scale manufacturing in the Northern Extended Bangkok Metropolitan Region mostly relate to the major city, Bangkok. In addition, there are other linkages between other cities located along the Phaholyothin Road, such as Ransit, Muang Pathum Thani, and Khong Luang. These cities are in the Desakota zone which extended to some parts of Phra Nakhorn Sri Ayuttaya. Furthermore, the study finds that the Eastern Extended Bangkok Metropolitan Region along Bangna-Trad Road, covering Samut Prakan, Chon Buri, and Rayong provinces, is considerably significant to the rural small-scale manufacturing as well. As a result, it is concluded that the rural-urban linkages pertaining to rural small-scale manufacturing in the study area has a connection with both the Northern Extended Bangkok Metropolitan Region and the Eastern Extended Bangkok Metropolitan Region. It is suggested that there should be strategic plans for the administrative management of the extended metropolitan regions based on current trends in term of to control the industrial distribution, the infrastructure development and to promote the important local manufacturing. Also, the potential of rural-urban linkages pertaining to manufacturing in both regions can be a guideline in order to efficiently develop a policy framework for the extended metropolitan region in the future.